Answer: ok LOL thx XD
Step-by-step explanation: BRAINLIEST PLS
Answer:
g(1) = 0
=
lgn= ) +m
g(n) = g(n - 1) +n
=
-
n
g(2) =12
Step-by-step explanation:
12345678910
<span>A) 2a + 3b = 12
B) ab = 6 solving for a
B) a = 6 / b then we substitute this into equation A)
</span><span>A) 12 / b + 3b = 12 </span><span>multiplying this by "b"
A) 12 + 3b^2 = 12b
A) 3b^2 -12b +12= 0 dividing by "3"
A) b^2 -4b + 4 = 0
Factoring
(b-2) * (b-2) = 0
b = 2
Since b = 2 then a = 3
</span>NOW, we put these numbers into:
<span>8a^3 +27b^3
</span>
8*3*3*3 + 27*2*2*2
216 + 216
The answer is 512
Answer:
1840
Step-by-step explanation:
Answer: X= 3.75
HOPE THIS HELPS:)))))
Step-by-step explanation: